The Dynamic Impact of Trade and Financial Globalization on Economic Growth in the North African Countries: Evidence from PMG-ARDL Model - Abd-Alkareem, Motaz (The Arab Journal of Administration, 2024)
This paper investigates the impact of trade and financial globalization on economic growth by employing Pooled Mean Group Autoregressive distributive lag (PMG-ARDL) model. The study uses the panel data of North African countries from 1980 to 2021. The findings show statistically significant evidence in favor of the existence of a long-run cointegrating relationship between the variables. In addition, the results show a positive impact of trade and financial globalization on economic growth in the long-run such that a 1% increase in trade globalization leads to 0.19% increase in economic growth, and a 1% increase in financial globalization results in 0.11% increase in economic growth. In the short-run, coefficients are not significant. As a further robustness check the Fully Modified Ordinary Least Square (FMOLS), and the Dynamic Ordinary Least Square (DOLS) are also used. The results are consistent with the PMG estimator. Last, these findings have some policy implications.